Analisis Yuridis Terhadap Uang Pengganti Untuk Pengembalian Kerugian Negara Dalam Perkara Tindak Pidana Korupsi Di Pengadilan Negeri Pekanbaru - Syahrial Syahrial; Maya Intan Pratiwi; Yonar Harada Taquas Elta (Journal of Legal Sustainability, 2026)
Replacement money is a consequence of the consequences of corruption that can harm the State or state economy, so to restore the loss is necessary juridical means in the form of payment of replacement money. The main problem in this research is how is the mechanism of payment of surrogate money for the return of state losses in the case of corruption crime in Pekanbaru District Court and what are the obstacles faced in the process of payment of replacement money for the return of state loss in the case of corruption in Pekanbaru District Court. The research results show that the mechanism for paying compensation to recoup state losses due to corruption in the Pekanbaru District Court is implemented after a final and binding decision through the confiscation of assets resulting from corruption. Additional penalties in the form of compensation may be imposed in the amount of the assets obtained from the corruption. The Prosecutor's Office implements this through collection, asset auctions, payment of compensation, and civil lawsuits. Obstacles include the difficulty of tracking diverted or spent assets, the inability of convicts to pay, and third-party lawsuits against confiscated assets.